Genome-Wide Identification of Immune-Related Alternative Splicing and Splicing Regulators Involved in Abdominal Aortic Aneurysm - Wu, Shiyong; Liu, Shibiao; Chen, Ningheng; Zhang, Chuang; Zhang, Hairong; Guo, Xueli (Frontiers in Genetics, 2022)
The molecular mechanism of AAA formation is still poorly understood and has not been fully elucidated. The study was designed to identify the immune-related genes, immune-RAS in AAA using bioinformatics methods. The GSE175683 datasets was downloaded from GEO database. DEseq2 software was used to identify differentially expressed genes. SUVA pipeline was used to quantify AS events and RAS events. KOBAS 2.0 server was used to identify GO terms and KEGG pathways to sort out functional categories of DEGs. The CIBERSORT algorithm was used with the default parameter for estimating immune cell fractions. 9 samples from GSE175683 were used to construct the co-disturbed network between expression of SFs and splicing ratio of RAS events. PCA analysis was performed by R package factoextra to show the clustering of samples and the pheatmap package in R was used to perform the clustering based on Euclidean distance. The results showed that there were 3541 genes significantly differentially expressed, of which 176 immune-related genes were up-regulated and 48 immune-related genes were down-regulated between WT and WTA group. Immune-RAS events were mainly alt5P and IR events and about 60% of it was complex splicing events in AAA. The WT group and the WTA group can be clearly distinguished in the first principal component by using the splicing ratio of immune-RAS events. Two downregulated genes, Nr4a1 and Nr4a2, and eight upregulated genes, Adipor2, Akt2, Bcl3, Dhx58, Pparg, Ptgds, Sytl1, and Vegfa were identified among the immune-related genes with RAS and DEGs. Eighteen differentially expressed SFs were identified and displayed by heatmap. The proportion of different types of cells and ratio of the average ratio of different cells were quite different. Both M1 and M2 types of macrophages were up-regulated, while M0 type was down-regulated in AAA. The proportion of plasma cells in the WTA group had sharply increased. There is a correlation between SF expression and immune cells. Sf3b1, a splicing factor with significantly different expression, was selected to analyzed and bound on a mass of immune-related genes. In conclusion, our results showed immune-related genes, immune-RAS and SFs by genome-wide identification were involved in AAA.